DDD Infrastructure library on .NET Core platform using MongoDB - Dužij, Maxim (2020)
DDD (Domain-Driven Design) is a popular approach to complex software development. However, there are many ways to implement such approach on .NET Core platform using MongoDB database.Main goal of this bachelor thesis is a creation of a framework that could help me, as a developer, speed up early development and use DDD approach in my .NET application. The Framework will include not only common DDD objects and interfaces (typed identifiers, domain aggregates and domain events) but also include persistence layer where It will use MongoDB database engine.Part of this bachelor work will also include sample Library domain and Library client application (Razor pages) what will use the framework and demonstrate basic principles of DDD.